Analysis of Estimation of Education Unit Costs (Micro Approach and Macro Approach) - Hayatunnida Jihan; Shaleh Shaleh (Journal of Educational Management Research, 2022)
Education funds are costs that are allocated individually to meet the educational needs of children in the future. The key to success in setting up an education fund is very simple. So start preparing now and do it consistently for the duration needed by estimating costs. Estimating the cost of education will help in estimating the funds needed for the level of education, this will predict unexpected economic turmoil in the future. Cost estimation with a micro approach calculates costs based on expenditure allocations. Strategies that can be used to estimate the estimated cost of education are (1) Cost Estimation Based on Funding Sources, and (2) Using direct reports from educational institutions. The tuition fee structure is structured as follows, (1) training unit costs, (2) personal costs, (3) organizational costs and (4) training unit administration. Expenditure allocations are broken down into independently quantifiable education items (building blocks) for students, such as social assistance, teacher instruction time, and course materials.